2017
DOI: 10.1159/000481699
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Expression Profile of the Myocardial Tissue of Pigs with Coronary Microembolization

Abstract: Background/Aims: Coronary microembolization (CME) is a serious complication of coronary heart disease and is considered as a strong predictor of poor long-term prognosis and major cardiac adverse events. Here, we identified differentially expressed microRNAs (miRNAs) in the myocardial tissue of CME pigs, and predicted and analyzed the possible functions of their target genes. Methods: Twelve Bama mini-pigs were randomly assigned to the sham and CME group (n = 6 in each group). The two groups were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Currently, it is believed that the inflammatory response in the myocardium might be the main cause of progressive systolic dysfunction [3,19]. Our previous animal experiments demonstrated that large amounts of inflammatory cells infiltrate micro-infracted lesions in the myocardium after CME, accompanied with a massive release of inflammatory factors, leading to local inflammatory response in the myocardium; this could be considered the central cause of myocardial injury and progressive cardiac dysfunction after CME [20,21]. Further experiments found that inflammatory factors in myocardial tissues, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is believed that the inflammatory response in the myocardium might be the main cause of progressive systolic dysfunction [3,19]. Our previous animal experiments demonstrated that large amounts of inflammatory cells infiltrate micro-infracted lesions in the myocardium after CME, accompanied with a massive release of inflammatory factors, leading to local inflammatory response in the myocardium; this could be considered the central cause of myocardial injury and progressive cardiac dysfunction after CME [20,21]. Further experiments found that inflammatory factors in myocardial tissues, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Very little research has focused on the expression of miR-136-3p in human or experimental CAD. A previous study on atherosclerosis has indicated that miR-136 was abnormally expressed in vascular smooth muscle cells, and its alteration mediates atherosclerosis through the influence on cell proliferation [14], and ssc-miR-136 has been reported to be broadly decreased in the myocardial tissue of pigs with coronary microembolization [33]. In this current study, we revealed that upregulation of miR-136-3p diminished the cardiomyocyte apoptosis in CAD rat models, as evidenced by lowered cleaved-caspase-3 and Bax as well as increased expression of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Gtl2/Meg3 lncRNA is downregulated in pulmonary smooth muscle cells subjected to hypoxia [ 100 ]. Consistent with these findings, lung tissue and pulmonary arteries from patients with pulmonary arterial hypertension (PAH) displayed reduced Gtl2/Meg3 expression [ 80 ]. Inhibition of Gtl2/Meg3 has been shown to promote proliferation of human pulmonary artery smooth muscle cells via the PTEN and p53 pathways, respectively [ 100 , 101 ].…”
Section: Long Noncoding Rnas Expressed From the Dlk1-diomentioning
confidence: 84%
“…In this same study, overexpression of miR-433 promoted cardiac fibroblast proliferation, and promoted pathological differentiation of fibroblasts into myofibroblasts [ 79 ]. Finally, miR-370 and miR-323 were upregulated in myocardial tissue from pigs subjected to coronary microembolization [ 80 ]. miR-370 was also expressed at significantly high levels in plasma from patients with coronary artery disease [ 81 ].…”
Section: Micrornas Expressed From the Dlk1-dio3 mentioning
confidence: 99%